2017
DOI: 10.1101/125054
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Long-term memory in the migration movements of enucleatedAmoeba proteus

Abstract: How motile, free unicellular organisms maximize the rate at which they encounter resources and develop optimal search strategies remains largely unknown. In fact, cell foraging is a very complex activity in which unicellular organisms integrate a diversity of external cues and develop efficient systemic movements to localize nourishment. These foraging strategies are critical when cells face conditions of scarce resources or they don't possess information on where food is located. Here, in order to determine w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
3
1

Relationship

4
0

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 31 publications
0
5
0
Order By: Relevance
“…As it has been pointed out in the chapter 5 of this review, several studies have already shown that motility patterns in enucleated cells does not significantly differ from the observed in normal cells on 2D surfaces [72,74]. In this sense, the works of De la Fuente et al [74,75] with eukaryotic unicellular organisms and of Graham et al [72] with mammalian cells, demonstrating that cell migration does not depend on the nucleus in 2D scenarios represents a great advance in the understanding of systemic control of cell motility.…”
Section: Discussionmentioning
confidence: 60%
See 2 more Smart Citations
“…As it has been pointed out in the chapter 5 of this review, several studies have already shown that motility patterns in enucleated cells does not significantly differ from the observed in normal cells on 2D surfaces [72,74]. In this sense, the works of De la Fuente et al [74,75] with eukaryotic unicellular organisms and of Graham et al [72] with mammalian cells, demonstrating that cell migration does not depend on the nucleus in 2D scenarios represents a great advance in the understanding of systemic control of cell motility.…”
Section: Discussionmentioning
confidence: 60%
“…on flat 2D surfaces using advanced non-linear physical-mathematical tools [74] ( Figure 1). The study had been previously deposited in bioRxiv.org by 2017 [75] and represents the first quantitative analysis of cell migration with enucleated cells.…”
Section: The Role Of the Nucleus In Cell Migrationmentioning
confidence: 99%
See 1 more Smart Citation
“…The nucleus has been classically considered an essential element governing cell movement, nevertheless direct quantitative evidence was lacking. The migratory analysis of enucleated and non-enucleated amoebae described above (Bringas et al, 2017;De la Fuente et al, 2019b;De la Fuente and López, 2020) also demonstrated that the absence of nucleus does not impact the systemic movements of amoebae significantly. An independent group has reached a similar conclusion using other experimental methods in human cells (Graham et al, 2018).…”
Section: Hopfield-like Dynamics and Associative Memorymentioning
confidence: 86%
“…Likewise, similar correlations have been observed in other different cellular processes not related to the neuronal lineage 10 . Finally, the presence of nontrivial correlations in the hunting movements of enucleated Amoeba proteus has been recently verified 11 .…”
Section: Conditioned Behavior Testmentioning
confidence: 88%